Spinal muscular atrophy in an upper-middle-income nation before the advent of reimbursed disease-modifying therapies - Kamornwan Katanyuwong; Utcharee Intusoma; Kullasate Sakpichaisakul; Tanitnun Paprad; Piradee Suwanpakdee; Chaiyos Khongkhatithum; Oranee Sanmaneechai (BMJ Publishing Group, 2024)
Objective To elucidate the clinical characteristics and standard of care (SoC) of spinal muscular atrophy (SMA) patients in Thailand, focusing on primary endpoints: age at death and a composite of death or tracheostomy need.Design Retrospective observational study.Setting Seven tertiary centres across Thailand.Patients Records of 110 patients with genetically confirmed SMA, spanning 2012-2021.Interventions Historical data review; no active interventions.Main outcome measures Age at death and a composite measure of death or tracheostomy necessity.Results The cohort included 1 SMA0, 50 SMA1, 40 SMA2 and 19 SMA3 cases. Median ages at the onset and diagnosis of SMA1 were 3 and 6.2 months. Of SMA1 patients, 63% required ventilators, and eight received dimethyltryptamines (DMTs) at a median of 15 months (range 6.4-24.5 months). The median time from onset to DMT was 11 months (range 4.2-20.5 months). Among SMA1 patients, 73% died by the study's end. SMA2 and SMA3 patients' median onset ages were 11 and 24 months, respectively, with diagnosis at 24.8 and 68.7 months. Half of all types received physical therapy.Conclusions Significant delays in diagnosis and SoC access, including DMTs, were observed, underscoring urgent needs for improved diagnostic and care strategies to enhance SMA patient outcomes in Thailand.